Power dependent upconversion in Er3+/Yb3+ co-doped BiNbO4 phosphors. Issue 6 (1st May 2016) - Sales, A.J.M.; Sousa, D.G.; Rodrigues, H.O.; Costa, M.M.; Sombra, A.S.B.; Freire, F.N.A.; Soares, M.J.; Graça, M.P.F.; Kumar, J. Suresh
Abstract: In the present article, optical properties and energy upconversion in Er 3+ /Yb 3+ co-doped BiNbO4 matrix were investigated. The BiNbO4 matrix was prepared using the solid-state reaction method. X-ray diffraction of the matrix shows that the crystal structure is consistent with ICSD code 74338. The grain distribution and the behavior of doping with Er 3+ and Yb 3+ on the sample surface were obtained by scanning electron microscope. Raman spectral characterization was carried out to examine the behavior of the vibrational modes of the samples. Upconversion emissions in the visible region at 484.5, 522, 541.5 and 670.5 nm in the matrices BiNbO4 :Er, Yb and BiNbO4 :Er were observed and analyzed as a function of 980 nm laser excitation power and rare-earth doping concentration. The results show that BiNbO4 is a promising host material for efficient upconversion phosphors.